The Golden Khersonese - Wheatley, Paul (University of Malaya Press, 2010)
This wholly admirable book by Professor Wheatley represents a major landmark in the study of Asian historical geography. The title, The Golden Khersonese, is derived from Ptolemy's Geography, and is in fact the name by which he and his contemporaries referred to the Malay peninsula south of the latitude of Cape Tavoy. Any scholar who seeks to reconstruct its early historical geography is beset by many problems which are largely unfamiliar to those of his fellows whose work is concentrated in the temperate occidental land of Europe or North America. And indeed, owing to the many and wide variations which this last fact entails in the mere transliteration of ordinary vernacular names, the key to the early historical geography of such an area as this lies, as the author says, in the identiﬁcation of place-names